Hubungan Manusia Dan Alam Perspektif Al-Qur’an - Mia Fitriah El-Karimah (Al Ashriyyah, 2020)
This writing is the result of a library research, that tries to examine how the relationship between nature and humans in the perspective of the Qur'an. It used in the perspective of the Qur'an through a thematic interpretation approach. The purpose is to find out how the Qur'an view the concepts of nature and humans. The relationship between humans and the universe that is in the Koran indicates the direction of humans who have a greater role in creating prosperity. human synergy as caliph on earth must follow the existing sunnatullah, must not violate, because this nature is objective, not favoritism, anyone who violates, will be subject to his punishment, whatever the reason for the violation, including ignorance or negligence.